Rare case of losartan-induced cough complicated by rectus sheath haematoma: in a patient on rivaroxaban therapy. (23rd December 2016) - Talari, Goutham; Talari, Preetham; Sweigart, Joseph; Ahmed, Sadiq
Abstract : Spontaneous rectus sheath haematomas and cough secondary to losartan are individually rare conditions. Abdominal wall haematomas present with abdominal pain and abdominal mass. Most patients are managed conservatively; Surgery or embolisation is indicated for shock, infection, rupture into the peritoneum or intractable pain. This is a man aged 65 years presented with dry cough and right-sided abdominal pain. He started losartan a few weeks prior to the onset of cough and had been on rivaroxaban for prior deep venous thrombosis. The right side of his abdomen was distended, bruised and tender. His haemoglobin dropped from 13.3to 9.5 g/dL. CT abdomen/pelvis showed a large 14.5×9.1×4.5 cm haematoma within the right lateral rectus muscle. His only risk factor for developing rectus sheath haematoma was cough in the setting of anticoagulation. Dry cough due to angiotensin receptor blockers is rare, but can have very serious consequences.